Guidance and Counselling Implications of Examination Anxiety as a Predictor of Students’ Attitude Towards Examination Malpractices - Ossai, Moses C. (Richtmann Publishing, 2011)
The study investigated the relationship between examination anxiety and students’ attitude towards examinationmalpractices in tertiary institutions in Delta State. The population of the study consisted of 12,000 first year regular students ineight tertiary invitations in Delta State. The proportional stratified sampling technique was used to select a sample size of 1,200subjects who responded to the Examination Anxiety and Attitude Questionnaire. Data collected was analyzed with correlationand multiple regression statistics and it was found that there is a positive relationship between examination anxiety and attitudetowards cheating in examinations. Students who possessed high examination anxiety were more predisposed towards cheatingin examinations. Therefore it was recommended that measures of examination anxiety could be used by Counsellors to identifystudents who were likely to engage in examination malpractices so that proactive therapies could be administered on them priorto their sitting for the actual examinations.